A Theoretical Model for Phagocytic Capacity of Phagocytes. Issue 2 (15th December 2022) - Guan, Jingjiao
Abstract: This work seeks to establish a theoretical model that links phagocytic capacity of phagocytes with geometries of phagocytes and phagocytic objects. The model is applied to four different types of phagocytic objects: a flat surface, a microsphere, a microdisk, and a population of microspheres. For the flat surface, the model assumes that a phagocyte maximizes its contact area between the flat surface and minimizes its non‐contact surface area under a constraint exerted by the volume of the phagocyte's cellular contents. For any of the other three types of objects, the model assumes that a phagocyte completely phagocytoses the object(s) by exhausting its available membrane area. It also assumes that the post‐phagocytosis phagocyte minimizes its surface area. Moreover, the volume of the phagocyte's cellular contents and the geometry of the object impose constraints on the model. For each case, two governing equations are established and combined to derive a single explicit equation with the phagocyte's phagocytic capacity as a function of other parameters. The equations are applied to experimental data for macrophages and neutrophils in the literature. Methods for extending the model and experimentally testing it are discussed. Abstract : Dependence of a phagocyte's phagocytic capacity on geometries of the phagocyte and phagocytic objects can be mathematically modeled by assuming that the phagocyte has a limited overall membrane area and tends to maximize its contact area with the object(s) and minimize its free surface area. This model is applied to objects with four different geometric shapes.